Conceptual basis that support the relationship between Knowledge and Patent (Research, Society and Development, 2022)
Interest in research related to knowledge and patentes has been growing in the academic and managerial environment. In order to contribute to the literature, this study uses bibliometric analysis, with a sample of 797 articles that relate knowledge and patents, extracted from the Web of Science database. In this study, the objective is to explore the conceptual bases on the relationship between knowledge and patents and answer the following question: what are the conceptual bases that support the relationship between knowledge and patents? Regarding the main findings, we highlight the hegemony of the United States in studies related to the topic, the evolution of China in recent years in this regard, in addition to the advances of Italy, with a significant number of studies in the third position. Another relevant point was the identification of an increase in the production of articles on knowledge by more than 70% in the last eight years (2013-2020). Regarding the main themes found in the analysis of factors, emphasis is given to: learning and organizational networks; innovation and geographic proximity; and patent and knowledge spillovers. In the end, the objectives of the study were achieved, with emphasis on the structuring of patent analysis over time and the trend of studies on geographic proximity and knowledge spillovers, when analyzing knowledge and patent. Other important findings of this research are: the sample of the main journals, authors, number of citations and co-citations, evolution of the research over time, in addition to indications about future studies.